Os 111 laudos necroscópicos do Carandiru: evidências de uma execução - Christovão, Nanci Tortoreto (2015)
The episode known as Carandiru Massacre resulted in at least 111 dead inmates. Their bodies were underwent thru autopsies by the Forensic Institute in São Paulo generating its reports. Since they were drafted, the forensic reports already recorded a range of data on victims and on the injuries that presented invaluable potential study. The second order observation conducted on those 111 forensic reports ,generating a variety of information that has been systematized and examined, comparing with other documents such as: the complaint lodged by the prosecution, testimony of surviving victims, the civilian police´s reports expertise, plus publications reporting on the facts and extracted news from newspapers and magazines. The meeting of these elements and their analysis allowed a better understanding of the police action that took on the afternoon of October 2nd, 1992, gaining more precise contours and allowing inferences about the implementing acts perpetrated by the police.